Respuesta del bovino Angus x Brahman sometido al fraccionamiento de la ración diaria en la ceba a corral - Bravo Pino, Jorge Eduardo (2016)
The objetive of this research was the evaluation of productive parameters of the breed Brangus submitted to ceba intensive during 90 days. Three treatment were used that corresponded to different schedules of feeding T1 06:00 – 12:00 – 18:00; T2 06:00 – 18:00; T3 08:00 – 16:00, each treatment cost a 10 Brangus steer lot, these animals were elected as homogeneous possible with an average weight of 360 kg. The variance of study were the productive indicator (weight gain each 14 days, cumulative weight gain, feed conversión and performance wing channel); estimating methane emissions and analysis cost - benefit. The results were evaluated with a block design presenting differences and study performance with the test of Tukey at a level of 95 % (P<0,001) for the T3 the weight gain was 92.10 kg in all of investigation 28.95 kg/kg with performance of the carcass 265.20 kg; no differences of weight gain of the steer but T3 was top in this variances of weight at 457.10 kg, T2 with a weight gain of 439.40 kg and this was low percentage. In conclusion three treatments were in the parameters settle down and refer to the variances of studied carefully getting the adequate treatment and the treatment T3 was top of the treatments with 65 %.